Dynamics of Islamic Boarding School Family Communication in Determining Political Affiliation - Ihwan Huda Al Mujib (Journal of Language, Communication, and Tourism, 2023)
The influence of Kyai and the pesantren family extends beyond religious and social realms and encompasses the political domain as well. The powerful influence of kyai and the pesantren has become a magnet for politicians not only for religious purposes, but political objectives as well. However, it is not easy for the kyai and pesantren families to decide on political affiliation. The dynamics of pesantren family communication occur in determining their political affiliation. This research was conducted using a qualitative approach and communication ethnography. The research was conducted in Islamic boarding schools families who were active in politics and had political affiliations. The results of the study show that the pesantren family has its own way of determining political affiliation. The dynamics of pesantren family communication in determining political affiliation can be a lesson for the wider community in determining political affiliation.